Modern principles of treatment of the serious multisystem injuries - A. V. Shteinle (Bûlleten' Sibirskoj Mediciny, 2009)
The analytical survey is concerned with the organizational aspects of the integrated study and thorough investigation of the problem of treatment of serious mechanical injuries.